Food Analysis Laboratory Manual - Nielsen, S. Suzanne (Springer, 2019)
This laboratory manual was written to accompany the textbook, Food Analysis, fifth edition. The laboratory exercises are tied closely to the text and cover 21 of the 35 chapters in the textbook. Compared to the second edition of this laboratory manual, this third edition contains four introductory chapters with basic information that compliments both the textbook chapters and the laboratory exercises (as described below). Three of the introductory chapters include example problems and their solutions, plus additional practice problems at the end of the chapter (with answers at the end of the laboratory manual). This third edition also contains three new laboratory exercises, and previous experiments have been updated and corrected as appropriate. Most of the laboratory exercises include the following: background, reading assignment, objective, principle of method, chemicals (with CAS number and hazards), reagents, precautions and waste disposal, supplies, equipment, procedure, data and calculations, questions, and resource materials.